Magnetic charcoal loaded cellulase compound taking bamboo as raw material as well as preparation method and application of magnetic charcoal loaded cellulase compound

The preparation of magnetic biochar-loaded cellulase complex by covalent precipitation method solves the problems of high cost and poor stability of immobilized cellulase carriers, and achieves low-cost and efficient cellulase immobilization and efficient catalysis, which improves the Biomass utilization efficiency.

CN119193568APending Publication Date: 2024-12-27SOUTH CHINA AGRICULTURAL UNIVERSITY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411481202.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The prior art has problems such as high cost, poor stability and low reuse rate in the selection and preparation of immobilized cellulases. Especially in the process of using lignocellulose hydrolysis, it is difficult to effectively improve the stability and repetition of the enzyme. Utilization.

Method used

Magnetic biochar-loaded cellulase complex was prepared by covalent precipitation method, and pyrolysis and ultrasonic dispersion were performed by mixing bamboo powder biochar with iron salt and anhydrous ethanol, followed by reaction with polyetherimide and glutaraldehyde. , chemically cross-linked to immobilize cellulases to form magnetic biochar-loaded cellulase complexes with high loading and stability.

Benefits of technology

Low-cost and efficient cellulase immobilization is achieved, the catalytic activity and stability of the enzyme is improved, the cost of cellulose hydrolysis is reduced, the high-value utilization ability of biomass is enhanced, and good reuse performance is demonstrated.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119193568A_ABST
    Figure CN119193568A_ABST
Patent Text Reader

Abstract

The invention discloses a magnetic charcoal-loaded cellulase compound taking bamboo as a raw material as well as a preparation method and application of the magnetic charcoal-loaded cellulase compound. The preparation method of the magnetic biochar loaded cellulase compound comprises the following steps: (1) uniformly mixing bamboo powder biochar, ferric salt and absolute ethyl alcohol to obtain a magnetic biochar precursor, and then heating to 300-500 DEG C for pyrolysis to obtain bamboo powder magnetic biochar; (2) modifying the bamboo powder magnetic biochar by using polyetherimide to obtain amino-modified bamboo powder magnetic biochar; then activating the bamboo powder magnetic biochar before or after amino modification with glutaraldehyde to obtain activated magnetic biochar; and (3) loading cellulase on the activated magnetic biochar to obtain the magnetic biochar loaded cellulase compound. The magnetic biochar prepared in the invention has strong loading capacity on cellulase, can improve the catalytic activity of the cellulase, and can be used for hydrolyzing cellulose to produce glucose.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of immobilized enzyme-catalyzed cellulose hydrolysis, and in particular to a magnetic biochar-loaded cellulase complex using bamboo as a raw material, and a preparation method and application thereof. Background Art

[0002] At present, the world's demand for energy is still huge, and due to the increasingly serious environmental pollution and other reasons, different types of sustainable new energy sources are gradually being valued by people and have become a current research hotspot. Biomass energy is a new form of energy that can synthesize natural cellulose through photosynthesis and then use solar energy to convert it into bioenergy stored in plants. It has huge development potential. Efficient enzymatic hydrolysis of lignocellulose to prepare reducing sugars is one of the research hotspots for high-value utilization of biomass.

[0003] Lignocellulose has the characteristics of wide sources, short regeneration cycle and low carbon content, and is an ideal raw material for the production of biomass-based materials, liquid fuels and high-value-added chemicals. The high-performance biochar prepared by incomplete carbonization has the advantages of strong adsorption, adjustable pore structure, good biocompatibility and easy recycling, and is an excellent carrier for immobilized enzymes. Therefore, using biochar as a carrier to achieve efficient immobilization of cellulase and explore the hydrolysis efficiency and reuse rate of biochar-immobilized cellulase will help promote the efficient utilization of biomass resources and the sustainable and healthy development of related enzyme industries.

[0004] The enzyme commonly used for hydrolysis of lignocellulose is cellulase, which is a protein that can break down cellulose into oligosaccharides and monosaccharides. The stability and activity of cellulase are key factors affecting the saccharification process of lignocellulose, which is affected by many factors such as the reaction system and reaction environment. Improving the recycling performance of cellulase is one of the main ways to reduce the production cost of related industries. In order to improve the efficiency of enzymatic hydrolysis, it is generally necessary to destroy the binding layer of lignin and hemicellulose, reduce the crystallinity of cellulose, reduce the content of lignin, control the generation of inhibitors, and select an appropriate pH value and enzymatic hydrolysis temperature.

[0005] Immobilized enzyme technology is a bioengineering technology that began in the 1960s. It can effectively improve the stability and reusability of enzymes. According to the composition of the carrier, immobilized enzyme carriers can be divided into organic carriers, inorganic carriers and metal organic framework carriers. Biochar materials belong to inorganic carrier materials. While having their own carrier properties, namely good stability, high mechanical strength, and low cost, they are similar to metal organic framework materials and have the advantages of controllable structure, large specific surface area and pore size, and good biocompatibility. Moso bamboo has the characteristics of rapid growth and strong environmental adaptability. The use of moso bamboo as raw material to prepare magnetic biochar has the advantages of sufficient raw materials, policy support, and low cost, which is conducive to the economic benefits and environmental advantages of sustainable development. Summary of the invention

[0006] The primary purpose of the present invention is to overcome the shortcomings and deficiencies of the prior art and to provide a method for preparing a magnetic biochar-loaded cellulase complex.

[0007] Another object of the present invention is to provide a magnetic biochar-loaded cellulase complex prepared by the method.

[0008] Another object of the present invention is to provide an application of the magnetic biochar loaded with cellulase complex.

[0009] The purpose of the present invention is achieved through the following technical solutions: A method for preparing a magnetic biochar-loaded cellulase complex comprises the following steps: (1) Preparation of magnetic biochar by “covalent precipitation method” ① Evenly mix bamboo powder biochar, iron salt and anhydrous ethanol to obtain a magnetic biochar precursor; wherein the iron salt is a mixture of divalent iron salt and trivalent iron salt; ② In a protective gas atmosphere, the magnetic biochar precursor obtained in step ① is heated to 300-500° C. for pyrolysis, and after the pyrolysis is completed, it is naturally cooled, and then taken out, ground, and washed to obtain bamboo powder magnetic biochar; (2) Preparation of magnetic biochar loaded with cellulase complex ③Ultrasonic dispersion of the bamboo powder magnetic biochar obtained in step ② and polyetherimide (PEI) in water, followed by shaking reaction at 60±5°C, collecting the material with a magnet after the reaction, washing, and drying to obtain amino-modified bamboo powder magnetic biochar; ④ Mixing the bamboo powder magnetic biochar obtained in step ② or the amino-modified bamboo powder magnetic biochar obtained in step ③ with a glutaraldehyde (GDA) solution for reaction, and washing after the reaction to remove unreacted glutaraldehyde to obtain activated magnetic biochar; ⑤ The activated magnetic biochar obtained in step ④ is evenly mixed with the cellulase solution, fixed by chemical bonding, and then the obtained product is magnetically separated and washed to obtain a magnetic biochar-loaded cellulase complex.

[0010] The bamboo powder biochar described in step ① is prepared from bamboo powder biochar using bamboo as raw material; preferably, it is prepared by the following method: The bamboo is crushed to obtain bamboo powder; the bamboo powder is then mixed with KOH and dissolved in water, and the mixed material is dried and heated to 300-500°C under a protective gas range for pyrolysis (activation), and after the pyrolysis is completed, it is washed to neutrality and dried to obtain bamboo powder biochar.

[0011] The bamboo is preferably moso bamboo; more preferably three-year-old moso bamboo.

[0012] The pulverization is performed to 40-100 meshes, preferably to 60 meshes.

[0013] The mass ratio of the bamboo powder to KOH is preferably 1:2.

[0014] The mass ratio of the bamboo powder to water is preferably 1:10.

[0015] The protective gas is N2, and its flow rate is 20 ml / min.

[0016] The heating rate is preferably 5°C / min.

[0017] The pyrolysis conditions are preferably: temperature 500°C, residence time 60 min.

[0018] The washing is carried out using deionized water.

[0019] The molar ratio of the divalent iron salt to the trivalent iron salt described in step ① is 1:2.

[0020] The divalent iron salt described in step ① is preferably FeCl2·4H2O (ferrous chloride tetrahydrate).

[0021] The trivalent iron salt described in step ① is preferably FeCl3·6H2O (ferric chloride hexahydrate).

[0022] The amount of bamboo powder biochar described in step ① is calculated based on 1g of bamboo powder biochar per mole of divalent iron salt.

[0023] The amount of anhydrous ethanol described in step ① is calculated based on 15-30 ml of anhydrous ethanol per gram of bamboo powder biochar; preferably, it is calculated based on 20 ml of anhydrous ethanol per gram of bamboo powder biochar.

[0024] The protective gas described in step ② is preferably nitrogen.

[0025] The heating rate in step ② is 8-12°C / min, preferably 10°C / min.

[0026] The pyrolysis method in step ② is preferably: first heating to 65-75°C and maintaining for 8-12 minutes, then continuing to heat to 300-500°C and maintaining for 50-70 minutes; more preferably: first heating to 70°C and maintaining for 10 minutes, then continuing to heat to 500°C and maintaining for 60 minutes.

[0027] The weight average molecular weight of the polyetherimide (PEI) described in step ③ is 10,000 to 20,000, preferably 10,000.

[0028] The mass ratio of the bamboo powder magnetic biochar to polyetherimide (PEI) described in step ③ is 1:5-10; preferably 1:5 or 1:10; more preferably 1:5.

[0029] The amount of water used in step ③ is calculated based on 15-30 mL of water per gram of bamboo powder magnetic biochar; preferably, it is calculated based on 20 mL of water per gram of bamboo powder magnetic biochar.

[0030] The water described in step ③ is deionized water.

[0031] The time of ultrasonic dispersion in step ③ can be set according to actual needs, preferably 10 min.

[0032] The reaction time in step ③ is 20 to 30 h, preferably 24 h.

[0033] The washing in step ③ is performed by alternately washing with deionized water and ethanol; preferably, the washing is performed by alternately washing with deionized water and ethanol for more than 3 times.

[0034] The drying method described in step ③ is: drying at 60±5°C for 10 to 15 h; preferably drying at 60°C for 12 h.

[0035] The concentration of the glutaraldehyde (GDA) solution in step ④ is 2-3% by volume, preferably 2.5% by volume.

[0036] The amount of glutaraldehyde (GDA) solution described in step ④ is calculated based on 20-40 mL of glutaraldehyde solution per gram of bamboo powder magnetic biochar (or amino-modified bamboo powder magnetic biochar); preferably, it is calculated based on 30 mL of glutaraldehyde solution per gram of bamboo powder magnetic biochar (or amino-modified bamboo powder magnetic biochar).

[0037] The reaction conditions in step ④ are: stirring the reaction at 20-30° C. for 1-3 hours; preferably stirring the reaction at 25° C. for 2 hours.

[0038] The washing in step ④ is performed using ionized water; preferably, the washing is performed using ionized water for more than 3 times.

[0039] The cellulase solution described in step ⑤ is prepared by the following method: dissolving the cellulase in a pH 5.0, 0.1 M acetic acid-sodium acetate buffer (weighing 0.8203 g of sodium acetate and making up to 100 ml).

[0040] The concentration of the cellulase solution in step ⑤ is 6-10 mg / mL; The reaction conditions in step ⑤ are: stirring the reaction at 20-30° C. for 1-3 hours; preferably: stirring the reaction at 25° C. for 2 hours.

[0041] The washing described in step ⑤ is performed using acetate buffer (0.05 mol / L, pH = 5).

[0042] A magnetic biochar-loaded cellulase complex is prepared by any of the methods described above.

[0043] The magnetic biochar-loaded cellulase complex is used in hydrolyzing cellulose (producing glucose).

[0044] Compared with the prior art, the present invention has the following advantages and effects: 1. The preparation method of the magnetic biochar loaded with cellulase provided by the present invention is simple. It uses iron salts ferric chloride hexahydrate (FeCl3·6H2O) and ferrous chloride tetrahydrate (FeCl2·4H2O) as magnetic media, and innovatively proposes a "covalent precipitation method" to prepare magnetic biochar.

[0045] 2. The present invention introduces magnetic biochar into the field of enzyme loading technology, and uses bamboo powder with low price and high yield as raw material, thereby reducing the preparation cost of biochar and magnetic carbon and realizing the resource utilization of low-cost materials.

[0046] 3. The present invention utilizes a chemical cross-linking method to load cellulase, and loads the cellulase on the surface of the magnetic biochar so that the two are tightly combined. The effective immobilization amount of cellulase is greatly increased by utilizing glutaraldehyde, and the hydrolysis efficiency of cellulose by the loaded cellulase is improved to a certain extent. The catalytic activity and operational stability of the enzyme are greatly improved and enhanced, and the advantages of immobilized enzymes in catalytic reactions compared to free enzymes are intuitively demonstrated.

[0047] 4. The present invention adopts the KOH activation method to increase the specific surface area of ​​biochar BC. Through the method of crushing-ketone alcohol extraction-hydrothermal pretreatment-KOH activation-carbonization, bamboo biochar material (BC) and eucalyptus biochar material (EC) with higher specific surface area were prepared, and their BET specific surface areas were measured. After KOH activation, the specific surface area of ​​bamboo biochar increased from 78 m 2 / g -1 Raised to 521 m 2 / g -1 .

[0048] 5. The bamboo magnetic biochar prepared in the present invention has a strong loading capacity for cellulase complexes and can be recycled. It has high catalytic activity and can be used to hydrolyze cellulose to produce glucose, thereby reducing the cost of cellulose hydrolysis, improving the utilization of cellulose, and thus achieving high-value utilization of biomass. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 The bamboo powder magnetic biochar Fe in the present invention 2+ and Fe 3+ Valence state distribution X-ray photoelectron spectroscopy (XPS) diagram.

[0050] Figure 2 It is the bamboo powder magnetic biochar prepared in the present invention and the magnetic regression curve (VSM) diagram (in the diagram, a represents the magnetic responsiveness performance of the magnetic biochar in deionized water).

[0051] Figure 3 It is a schematic diagram of the preparation process of fixing cellulase by the amino-modified chemical cross-linking method (amino-modified glutaraldehyde cross-linking method) of magnetic biocarbon in Example 1 of the present invention.

[0052] Figure 4 It is a schematic diagram of the preparation process of fixing cellulase by the magnetic biochar chemical cross-linking method (glutaraldehyde cross-linking method) in Example 2 of the present invention.

[0053] Figure 5 This is a graph showing the results of a study on the reuse performance of the magnetic biochar-loaded cellulase complex prepared in Examples 1 to 2 of the present invention and Comparative Example 1. DETAILED DESCRIPTION

[0054] The present invention will be described in further detail below in conjunction with the examples, but the embodiments of the present invention are not limited thereto. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art. The test methods for which specific experimental conditions are not specified in the following examples are usually carried out according to conventional experimental conditions or according to the experimental conditions recommended by the manufacturer. Unless otherwise specified, the reagents and raw materials used in the present invention can be obtained commercially.

[0055] The bamboo powder biochar materials involved in the embodiments and comparative examples of the present invention are prepared using moso bamboo as raw material: A mixture of bamboo powder and KOH solids with a mass ratio of 1:2 was added with deionized water with a mass ratio of 1:10 to the bamboo powder raw material to fully dissolve the KOH solid and mix it with the sample evenly; the bamboo powder was obtained as follows: three-year-old bamboo provided by Fujian Agriculture and Forestry University was crushed into 60 mesh size; the mixed material was then placed in an iron plate and put into an oven for drying; the dried sample was then placed in a tubular furnace for activation: under a N2 environment (N2 rate 20ml / min), heated to 500℃ at a heating rate of 5℃ / min, with a residence time of 60min; finally, the activated carbon was washed with deionized water until neutral and dried to obtain bamboo powder biochar.

[0056] The sodium carboxymethyl cellulose solution (CMC, 1%) involved in the examples and comparative examples of the present invention was purchased from Lianmai Biotechnology.

[0057] The cellulase involved in the examples and comparative examples of the present invention was purchased from Ningxia Heshibi Company (specification: 20000u / g).

[0058] The polyetherimide (PEI for short) involved in the examples and comparative examples of the present invention was purchased from MacLean (molecular weight: 10000 MW, purity: 99%).

[0059] Example 1 This embodiment provides a method for loading cellulase onto magnetic biochar made of bamboo as raw material by chemical cross-linking of biochar modified with amino groups ( Figure 3 ), the specific steps are as follows: (1) Preparation of magnetic biochar by “covalent precipitation method” Step 1, preparation of magnetic biochar precursor: weigh 0.1 g of bamboo powder biochar material, add a certain amount of iron salt (0.2 mol FeCl3·6H2O and 0.1 mol FeCl2·4H2O, molar ratio 2:1) and 2 ml of anhydrous ethanol and mix well to obtain a magnetic biochar precursor.

[0060] Step 2, preparation of bamboo powder magnetic biochar: placing the magnetic biochar precursor in a tube furnace, under nitrogen protection, first heating it to 70 °C at a heating rate of 10 °C / min and holding it for 10 minutes, then continuing to heat it to 500 °C and holding it for 1 hour, and then taking it out after natural cooling; finally, grinding and washing the product obtained by pyrolysis to obtain bamboo powder magnetic biochar. The bamboo powder magnetic biochar Fe 2+ and Fe 3+ Valence distribution Figure 1 When bamboo powder magnetic biochar is placed in deionized water, its magnetic responsiveness and magnetic regression curve are shown in Figure 2 shown.

[0061] (2) Preparation of magnetic biochar loaded with cellulase complex Step 3, amino-modified bamboo powder magnetic biochar: 1 g of the above-prepared bamboo powder magnetic biochar and 5 g of PEI were dispersed in 20 mL of deionized water and ultrasonically mixed for 10 min. Then it was transferred to a constant temperature water bath oscillator and oscillated at 60°C for 24 h. After the end, the material was collected with a magnet and washed alternately with deionized water and ethanol for 3 times, and finally dried at 60°C for 12 h to obtain amino-modified bamboo powder magnetic biochar.

[0062] Step 4, glutaraldehyde cross-linking: 1.0 g of the amino-modified bamboo powder magnetic biochar carrier was reacted with 30 mL of 2.5% (v / v) glutaraldehyde (GDA) solution and stirred at 25 °C for 2 hours to activate the carrier by providing aldehyde groups; the GDA-activated carrier was then washed three times with deionized water to remove unreacted GDA to obtain activated magnetic biochar.

[0063] Step 5, chemical binding and immobilization of cellulase: Weigh 50 mg of the activated magnetic biochar sample and mix it with 10 mL of 6 mg / mL cellulase solution (dissolve the cellulase in pH 5.0, 0.1 M acetic acid-sodium acetate buffer (weigh 0.8203 g of sodium acetate and make up to 100 ml)), gently stir at 25 ° C for 2 hours, and fix it by chemical binding. Finally, the product was separated by magnetic separation and washed with acetate buffer (0.05 mol / L, pH = 5) to remove the unimmobilized cellulase, and the magnetic biochar-loaded cellulase complex was obtained.

[0064] (3) Determination of cellulase loading Step 6, when the set immobilization time is reached, after separation with a magnet, 0.2 mL of supernatant is drawn from the centrifuge tube, and then 0.8 mL of acetate buffer (0.05 mol / L, pH = 5) is added to dilute 5 times, and then the ultraviolet absorption value at the maximum peak of 264 nm is measured using an ultraviolet spectrophotometer; the cellulase concentration is determined by the Bradford protein assay, and the ultraviolet absorption value is brought into the established cellulase standard curve to calculate the cellulase concentration in the supernatant, and the cellulase immobilization amount is calculated by the formula, in units of mg / g (cellulase immobilization amount = C0V0-C1V1, where C0 and V0 are the concentration and volume of the initial cellulase solution, respectively, and C1 and V1 are the concentration and volume of the immobilized cellulase solution, respectively). The average value of three measurements is taken.

[0065] (4) Performance testing Step 7, catalytic cellulose hydrolysis performance test: 10 mg of magnetic biochar loaded cellulase complex was mixed with 0.1% (w / w) cellulose reaction substrate (sodium carboxymethyl cellulose CMC solution), and then 10 ml (0.05 mol / L, pH = 5) of acetate buffer was added to a 50 ml centrifuge tube. After mixing evenly, it was placed in a constant temperature air bath oscillator, and the reaction conditions were 50 ° C and 120 rpm / min. 0.2 ml of the supernatant was taken at 1 h, 2 h, 3 h, 4 h, and 5 h, respectively, and after diluting 5 times, it was injected into HPLC (flow rate 0.4 ml / min, mobile phase: 0.1 mol / l NaOH, temperature: 35 ° C) to determine its glucose content. The experiment was repeated three times. From the experimental results, we can see that the glucose content after 1 hour of reaction is 5-5.5 mg / ml, after 2 hours of reaction, the glucose content is 5.5-7 mg / ml, after 3 hours of reaction, the glucose content is 7-8 mg / ml, after 4 hours of reaction, the glucose content is 8-9 mg / ml, and after 5 hours of reaction, the glucose content is 9-10 mg / ml.

[0066] Step 8, after recovering the magnetic biochar loaded with cellulase complex, perform a cellulose hydrolysis repeatability experiment: take 5 mg of the immobilized enzyme sample recovered after 5 h of hydrolysis in step 7, add 10 ml (0.05 mol / L, pH = 5) of acetate buffer in a 50 ml centrifuge tube, mix well and place in a constant temperature air bath oscillator, at 50 ° C, 120 rpm / min reaction conditions. After 24 h of reaction, take 0.2 ml of the supernatant, dilute 5 times, inject into HPLC (flow rate 0.4 ml / min, mobile phase: 0.1 mol / lNaOH, temperature: 35 ° C), determine its glucose content, and set the experiment to repeat three times; after the remaining product is separated from the solid by an external magnet, the product is collected and rinsed with acetate buffer 2 to 3 times, and then the substrate is re-added for hydrolysis according to the method in step 7, and this is repeated 5 times to determine the glucose content. The experimental results show that the glucose content after one cycle is 8-9 mg / ml, the glucose content after two cycles is 8-8.5 mg / ml, and the glucose content after three cycles is 7-8 mg / ml ( Figure 5 ).

[0067] Example 2 This embodiment provides a method for loading cellulase onto magnetic biochar made of bamboo using a chemical cross-linking method ( Figure 4 ), the specific steps are as follows: (1) Preparation of magnetic biochar by “covalent precipitation method” Step 1, preparation of magnetic biochar precursor: weigh 0.1 g of bamboo powder biochar material, add a certain amount of iron salt (0.2 mol FeCl3·6H2O and 0.1 mol FeCl2·4H2O) and 2 ml of anhydrous ethanol and mix well to obtain a magnetic biochar precursor.

[0068] Step 2, preparation of bamboo powder magnetic biochar: placing the magnetic biochar precursor in a tubular furnace, under nitrogen protection, first heating it to 70 °C at a heating rate of 10 °C / min and keeping it for 10 minutes, then continuing to heat it to 500 °C and keeping it for 1 hour, and then taking it out after natural cooling; finally, grinding and washing the product obtained by pyrolysis to obtain bamboo powder magnetic biochar.

[0069] (2) Preparation of magnetic biochar loaded with cellulase complex Step 3, glutaraldehyde cross-linking: 1.0 g of bamboo powder magnetic biochar carrier was reacted with 30 mL of 2.5% (v / v) glutaraldehyde (GDA) solution and stirred at 25 °C for 2 hours to activate the carrier by providing aldehyde groups; the GDA-activated carrier was then washed three times with deionized water to remove unreacted GDA and obtain activated magnetic biochar.

[0070] Step 4, chemical binding and immobilization of cellulase: Weigh 50 mg of the activated magnetic biochar sample, dissolve the cellulase in pH = 5, 0.1 M acetic acid-sodium acetate buffer, prepare 6 mg / ml and 10 mg / ml cellulase solutions, and take 10 ml of the cellulase solution and mix it with the activated magnetic biochar. Stir gently at 25 ° C for 2 hours and fix it by chemical binding. Finally, the product is recovered by magnetic separation and washed with acetate buffer (0.05 mol / l, pH = 5) to remove the unimmobilized cellulase to obtain a magnetic biochar-loaded cellulase complex.

[0071] (3) Determination of cellulase loading: The determination method is the same as in Example 1.

[0072] (4) Performance testing Step 5, catalytic cellulose hydrolysis performance test (the cellulase solution used is 10 mg / ml): the treatment method is the same as Example 1. From the experimental results, it can be seen that the glucose content after 1 hour of reaction is close to 4-6 mg / ml, the glucose content after 2 hours of reaction is close to 5-8 mg / ml, the glucose content after 3 hours of reaction is close to 7-9 mg / ml, the glucose content after 4 hours of reaction is close to 8-10 mg / ml, and the glucose content after 5 hours of reaction is close to 8-10 mg / ml.

[0073] Step 6, after recovering the magnetic biochar loaded with cellulase complex, a cellulose hydrolysis repeatability experiment is conducted (the cellulase solution used is 10 mg / ml): the treatment method is the same as in Example 1. The experimental results show that the glucose content after one cycle is 8-10 mg / ml, the glucose content after two cycles is 7-9 mg / ml, and the glucose content after three cycles is 6-8.5 mg / ml ( Figure 5 ).

[0074] Comparative Example 1 In this comparative example, cellulase is loaded onto magnetic biochar using bamboo as raw material by physical method, and the specific method steps are as follows: (1) Preparation of magnetic biochar by “covalent precipitation method” Step 1, preparation of magnetic biochar precursor: weigh 0.1 g of bamboo powder biochar material, add a certain amount of iron salt (0.2 mol FeCl3·6H2O and 0.1 mol FeCl2·4H2O) and 2 ml of anhydrous ethanol and mix well to obtain a magnetic biochar precursor.

[0075] Step 2, preparation of bamboo powder magnetic biochar: placing the magnetic biochar precursor in a tubular furnace, under nitrogen protection, first heating it to 70 °C at a heating rate of 10 °C / min and keeping it for 10 minutes, then continuing to heat it to 500 °C and keeping it for 1 hour, and then taking it out after natural cooling; finally, grinding and washing the product obtained by pyrolysis to obtain a magnetic biochar carrier.

[0076] (2) Preparation of magnetic biochar loaded with cellulase complex Step 3, magnetic biochar loaded with cellulase: a mixed solution of 0.1 g of magnetic biochar carrier and 10 mL of 4 mg / mL cellulase solution (cellulase was dissolved in pH 5.0, 0.1 M acetic acid-sodium acetate buffer (0.8203 g of sodium acetate was weighed and fixed to 100 ml)) was placed in a constant temperature air bath shaker, the temperature was set to 50 °C, and the sample was taken after shaking at 120 r / min for 12 hours; (3) Determination of cellulase loading: The determination method is the same as in Example 1.

[0077] (4) Performance testing Step 5, catalytic cellulose hydrolysis performance test: the treatment method is the same as Example 1. From the experimental results, it can be seen that the glucose content is 2.8-2.9 mg / ml after 1 hour of reaction, the glucose content is 2.9-3.0 mg / ml after 2 hours of reaction, the glucose content is 3.5-4.0 mg / ml after 3 hours of reaction, the glucose content is 4.0-5.1 mg / ml after 4 hours of reaction, and the glucose content is 4.8-6.0 mg / ml after 5 hours of reaction.

[0078] Step 6, recovering the magnetic biochar loaded with cellulase complex and conducting a cellulose hydrolysis repeatability experiment: the treatment method is the same as in Example 1. The experimental results show that the glucose content after one cycle is 4-6 mg / ml, the glucose content after two cycles is 4-5 mg / ml, and the glucose content after three cycles is 3.5-4 mg / ml ( Figure 5 ).

[0079] Effect Example The enzyme loading amount and enzyme activity of the magnetic biochar-loaded cellulase complex prepared in Examples 1-2 and Comparative Example 1 were measured. Each group of experiments was measured three times and the average value was taken. The results are shown in Table 1.

[0080] Table 1 Enzyme loading and enzyme activity of magnetic biochar-loaded cellulase complexes prepared by three different methods Note: “Sample 1” and “Sample 2” in Table 1 are both repeated experimental samples.

[0081] In summary: A longitudinal comparison of several methods shows that the enzyme loading amounts of the methods are not much different, but there are differences in enzyme activity. The magnetic biocarbon immobilization enzyme prepared by the conventional physical method has the lowest enzyme activity, while the present invention adopts the amino modification-glutaraldehyde cross-linking method and the glutaraldehyde cross-linking method of cellulase reaction to prepare, and the cellulase activity is higher than that of the physical method, among which the enzyme activity of the glutaraldehyde cross-linking method of cellulase reaction can reach 4032 U / g (Table 1).

[0082] In addition, the content of glucose produced by catalyzing cellulose hydrolysis after three times of reuse of magnetic biochar-loaded cellulase complexes prepared by three different methods showed that the efficiency of cellulose hydrolysis catalyzed by magnetic biochar-immobilized cellulase decreased with the increase of the number of cycles ( Figure 5 ). The overall catalytic efficiency of the two magnetic biocarbon immobilization enzymes prepared by the present invention is higher than that of the physical method. At the same time, as the number of cycles increases, the extent of the decrease in hydrolysis efficiency is also smaller than that of the physical method, and the decrease in glucose concentration in the product between two times is less than 1 mg / ml. Therefore, it is shown that the preparation of the present invention has a good prospect for recycling.

[0083] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a magnetic biochar-loaded cellulase complex, characterized in that: The steps include: (1) Preparation of magnetic biochar by "covalent precipitation method" ① Evenly mix bamboo powder biochar, iron salt and anhydrous ethanol to obtain a magnetic biochar precursor; wherein the iron salt is a mixture of divalent iron salt and trivalent iron salt; ② In a protective gas atmosphere, the magnetic biochar precursor obtained in step ① is heated to 300-500° C. for pyrolysis, and after the pyrolysis is completed, it is naturally cooled, and then taken out, ground, and washed to obtain bamboo powder magnetic biochar; (2) Preparation of magnetic biochar loaded with cellulase complex ③ Ultrasonic dispersion of the bamboo powder magnetic biochar obtained in step ② and polyetherimide in water, followed by shaking reaction at 60±5° C. After the reaction is completed, the material is collected with a magnet, washed, and dried to obtain amino-modified bamboo powder magnetic biochar; ④ Mixing the bamboo powder magnetic biochar obtained in step ② or the amino-modified bamboo powder magnetic biochar obtained in step ③ with a glutaraldehyde solution for reaction, and washing after the reaction to remove unreacted glutaraldehyde to obtain activated magnetic biochar; ⑤ The activated magnetic biochar obtained in step ④ is evenly mixed with the cellulase solution, fixed by chemical bonding, and then the obtained product is magnetically separated and washed to obtain a magnetic biochar-loaded cellulase complex.

2. The method according to claim 1, characterized in that: The molar ratio of the divalent iron salt to the trivalent iron salt described in step ① is 1:2; The weight average molecular weight of the polyetherimide described in step ③ is 10000 to 20000; The mass ratio of the bamboo powder magnetic biochar to the polyetherimide in step ③ is 1:5-10; The concentration of the glutaraldehyde solution described in step ④ is 2-3% by volume; The concentration of the cellulase solution in step ⑤ is 6-10 mg / mL.

3. The method according to claim 2, characterized in that: The weight average molecular weight of the polyetherimide described in step ③ is 10000; The mass ratio of the bamboo powder magnetic biochar to the polyetherimide in step ③ is 1:5; The concentration of the glutaraldehyde solution described in step ④ is 2.5% by volume.

4. The method according to claim 1, characterized in that: The divalent iron salt described in step ① is FeCl2·4H2O; The trivalent iron salt described in step ① is FeCl3·6H2O.

5. The method according to claim 1, characterized in that: The heating rate in step ② is 8-12°C / min; The pyrolysis method described in step ② is: firstly heat up to 65-75°C and keep for 8-12 minutes, then continue to heat up to 300-500°C and keep for 50-70 minutes.

6. The method according to claim 1, characterized in that: The bamboo powder biochar described in step ① is prepared by the following method: crushing bamboo to obtain bamboo powder; then mixing the bamboo powder with KOH and dissolving it in water, drying the mixed material and heating it to 300-500° C. under a protective gas range for pyrolysis, washing to neutrality after the pyrolysis is completed, and drying to obtain bamboo powder biochar; The bamboo is Phyllostachys pubescens.

7. The method according to claim 1, characterized in that: The amount of the glutaraldehyde solution in step ④ is calculated based on 20-40 mL of glutaraldehyde solution per gram of bamboo powder magnetic biochar or amino-modified bamboo powder magnetic biochar; The cellulase solution described in step ⑤ is prepared by the following method: dissolving the cellulase in a pH 5.0, 0.1 M acetic acid-sodium acetate buffer.

8. The method according to claim 1, characterized in that: The reaction time in step ③ is 20 to 30 h; The washing in step ③ is washing with deionized water and ethanol alternately; The drying method described in step ③ is: drying at 60±5℃ for 10-15 hours; The reaction conditions in step ④ are: stirring the reaction at 20-30° C. for 1-3 hours; The washing in step ④ is performed by washing with ionized water; The reaction conditions in step ⑤ are: stirring the reaction at 20-30° C. for 1-3 hours; The washing in step ⑤ is performed using an acetate buffer solution with a pH of 5 and a concentration of 0.05 mol / L.

9. A magnetic biochar loaded cellulase complex, characterized in that: It is prepared by the method according to any one of claims 1 to 8.

10. Use of the magnetic biochar loaded cellulase complex according to claim 9 in hydrolyzing cellulose.

Citation Information

Cited By

  • Fe-doped biochar field-oriented enhanced conductive cement-based composite material and preparation method thereof

    CN121494448A